OCCURRENCE OF METAPENAEOPSIS HlLARULA (DE MAN) AND PENAEUS PENICILLATUS ALCOCK (DECAPODA: PENAEIDAE) IN COCHIN BACKWATER - Kathirvel, M; Gopalakrishnan, K N; Nalini, C (Indian Journal of Fisheries, 2011)
The occurrence of Melnpenneopsis hilarula (de Man) and Penaeus penicillatusAlcock from Cochin Backwater is reported for the first-time.